Genetic diversity and core subset selection in ex situ seed collections of the banana crop wild relative Musa balbisiana. Issue 6 (29th December 2019) - Bawin, Yves; Panis, Bart; Vanden Abeele, Samuel; Li, Zhiying; Sardos, Julie; Paofa, Janet; Ge, Xue-Jun; Mertens, Arne; Honnay, Olivier; Janssens, Steven B.
Abstract: Crop wild relatives (CWRs) play a key role in crop breeding by providing beneficial trait characteristics for improvement of related crops. CWRs are more efficiently used in breeding if the plant material is genetically characterized, but the diversity in CWR genetic resources has often poorly been assessed. Seven seed collections of Musa balbisiana, an important CWR of dessert and cooking bananas, originating from three natural populations, two feral populations and two ex situ field collections were retrieved and their genetic diversity was quantified using 18 microsatellite markers to select core subsets that conserve the maximum genetic diversity. The highest genetic diversity was observed in the seed collections from natural populations of Yunnan, a region that is part of M. balbisiana 's centre of origin. The seeds from the ex situ field collections were less genetically diverse, but contained unique variation with regards to the diversity in all seed collections. Seeds from feral populations displayed low genetic diversity. Core subsets that maximized genetic distance incorporated almost no seeds from the ex situ field collections. In contrast, core subsets that maximized allelic richness contained seeds from the ex situ field collections. We recommend the conservation and additional collection of seeds from natural populations, preferentially originating from the species' region of origin, and from multiple individuals in one population. We also suggest that the number of seeds used for ex situ seed bank regeneration must be much higher for the seed collections from natural populations.